2016
DOI: 10.1118/1.4944866
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral perfusion computed tomography deconvolution via structure tensor total variation regularization

Abstract: This study demonstrated the feasibility and efficacy of the present PD-STV approach in utilizing STV regularization to improve the accuracy of residue function estimation of cerebral PCT imaging in the case of low-mAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…2 shows the digital brain perfusion phantom used in this study which consists of user-defined regions of white matter, gray matter, penumbra, and stroke core [12]. We simulated the same phantom with the size of 256×256×40 as the previous work [11], which was designed to simulate a complex structure in real human brain. Specifically, a fan-beam CT imaging geometry was used in the simulation study, and the imaging parameters are set as follows: (1) each scan includes 1160 projection views evenly distributed over 2 π , (2) the number of channels per view is 672, and (3) the source-to-axis distance is 570 mm and the source-to-imager is 1040 mm .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2 shows the digital brain perfusion phantom used in this study which consists of user-defined regions of white matter, gray matter, penumbra, and stroke core [12]. We simulated the same phantom with the size of 256×256×40 as the previous work [11], which was designed to simulate a complex structure in real human brain. Specifically, a fan-beam CT imaging geometry was used in the simulation study, and the imaging parameters are set as follows: (1) each scan includes 1160 projection views evenly distributed over 2 π , (2) the number of channels per view is 672, and (3) the source-to-axis distance is 570 mm and the source-to-imager is 1040 mm .…”
Section: Resultsmentioning
confidence: 99%
“…To reduce radiation dose, instead of scanning the monkeys twice, we simulated the low-dose DCPCT data from these acquired DCPCT data. For low-dose DCPCT data, we simulate them from the reference standard using the simulation technique based on [11] which is similar to the simulation in Sec. III-A, and the noise levels related to the projection data acquired about 50 mA at a fixed kV p were simulated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the clinic, the presented PWLS-aviNLM algorithm can be stretched into various applications, such as photon-counting CT imaging (Zhang et al 2016a, Zeng et al 2016b, Yu et al 2016), 4D CT/CBCT imaging (Dang et al 2016), and perfusion imaging (Fang et al 2015, Zeng et al 2016c), where redundant information can be observed among image data. Also, the aviNLM-based idea could be possibly used to solve the metal artifacts reduction problem (i.e., degraded projection that might be truncated due to strong attenuation or streak artifacts around metallic objects), because the vast body of external knowledge can be globally searched in the domain of the already acquired medical CT images.…”
Section: Discussionmentioning
confidence: 99%